Kualitas Air dan Pertumbuhan Ikan Nilem (Osteochilus vittatus) pada Sistem Resirkulasi dengan Media Filtrasi Berbeda - Nuning Setyaningrum; Muhammad Hussein Sastranegara; Firda Isdianto; Sugiharto Sugiharto (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
Nilem (Osteochilus vittatus) is a popular freshwater commodity. Intensive production of nilem is often limited by water quality degradation. Recirculating aquaculture system is known to have advantage over this problem. Zeolites and water spinach (Ipomoea aquatica) are widely used in water remediation effort. This research aimed to find out water quality and nilems’ growth in two distinct recirculating system (zeolite filter based recirculating system; water spinach based recirculating system) as well as the relation between these variables. Furthermore, the difference in water quality and nilem’s growth between the two recirculating system was also evaluated. The method used was a completely randomized experimental design with three replication. Nilems were reared in recirculating system with a density of 100 individuals for 60 days. Measurement of water quality and nilem’s growth was conducted on day 0, 30, and 60. The measured parameters included water temperature, TSS, DO, CO2, pH, NH3 and nilem’s weight. Analysis of data in was completely done with descriptive method. The result showed that water quality and nilem’s growth in recirculating system using zeolite filter and in recirculating system using water spinach filter was similar in general. Water quality in both recirculating system was sufficient to promote nilem’s growth.